Developmental Profile and Sexually Dimorphic Expression of Kiss1 and Kiss1r in the Fetal Mouse Brain - Knoll, John G.; Clay, Colin; Bouma, Gerrit; Henion, Timothy; Schwarting, Gerald; Millar, Robert; Tobet, Stuart (Frontiers in Endocrinology, 2013)
The hypothalamic-pituitary-gonadal axis (HPG) is a complex neuroendocrine circuit involving multiple levels of regulation. Kisspeptin neurons play essential roles in controlling the HPG axis from the perspectives of puberty onset, oscillations of gonadotropin releasing hormone (GnRH) neuron activity and the pre-ovulatory LH surge. The current studies focus on the expression of kisspeptin during murine fetal development using in situ hybridization (ISH), quantitative reverse transcription real-time PCR (QPCR) and immunocytochemistry. Expression of mRNA coding for kisspeptin (KISS1) and its receptor KISS1R was observed at embryonic (E) day 13 by ISH. At E13 and other later ages examined, Kiss1 signal in individual cells within the arcuate nucleus (ARC) appeared stronger in females than males. ISH examination of agonadal steroidogenic factor-1 (Sf1) knockout mice revealed that E17 XY knockouts resembled wild-type XX females. These findings raise the possibility that gonadal hormones modulate the expression of Kiss1 in the ARC prior to birth. The sex and genotype differences were tested quantitatively by QPCR experiments in dissected hypothalami from mice at E17 and adulthood. Females had significantly more Kiss1 than males at both ages, even though the number of cells detected by ISH was similar. In addition, QPCR revealed a significant difference in the amount of Kiss1 mRNA in Sf1 mice with wild-type (WT) XY mice expressing less than XY knockouts (KO) and XX mice of both genotypes. The detection of immunoreactive KISS1 in perikarya of the ARC at E17 indicates that early mRNA is translated to peptide. The functional significance of this early expression of Kiss1 awaits elucidation.